Pengaruh Perbedaan Konsentrasi Ekstrak Karapas Udang Terhadap Sifat Fisikokimia Kaldu Bubuk yang Dihasilkan - Siti Karomah; Sri Haryati; Sudjatinah Sudjatinah (Jurnal Teknologi Pangan dan Hasil Pertanian, 2021)
Shrimp carapace is one of the fisheries waste products that can be a potential alternative for natural flavoring because it contains a lot of glutamic acid that create umami taste in dishes by turning it into a powdered broth. Powdered broth is a product that has been known as a food additive that is obtained from boiling meat or more commonly known as a seasonings. The purpose of this study is to know how the effect and best treatment of different concentrations of extract from shrimp carapace on the quality of the resulting powder broth. This research was conducted at the Food Engineering Laboratory, Chemistry Laboratory Semarang university and the Chemix Pratama Laboratory Yogyakarta. The design of the experiment used was a completely randomized design with 5 treatments and 4 replications, which gives the concentration of shrimp carapace, which is 3%; 3.5%; 4%; 4.5%; And 5%. The test parameters were water levels, fat levels, protein levels, glutamate levels, and hedonic tests include taste and aroma attributes. To find out the difference between treatment, data was tested with Duncan multiple range test (DMRT) at 5% level. The results have shown that differences in shrimp carapace extract have a significant effect (p <0.05) on water levels, fat levels, protein levels, glutamate levels, and hedonic scores. This study recommends P3 treatment as the best alternative treatment considering water level (4,17%), fat content (1,29%), protein (15,05%), glutamate (10,76%), and being the most preferred by panelists. with the taste attribute score (5.50), and aroma (4.77).